Kesesuaian Sistem TIRADS Dengan Hasil Pemeriksaan Patologi Anatomi Nodul Tiroid - UTOMO, RADITYA (Indonesian Journal of Cancer, 2014)
Thyroid ultrasonography is the modality of choice to detect, and to evaluate the morphology of thyroid nodule. ThyroidImaging Reporting and Data System (TIRADS) is a system to evaluate risk of malignancy of thyroid nodule, that firstproposed by Horvath et al. There are various TIRADS proposed by other authors. To the author knowledge, until thewriting of this study there is not yet found a study to evaluate implementation and diagnostic value of TIRADS inIndonesian.Methods: Diagnostic study with cross sectional approach using retrospective evaluation of thyroid ultrasonographydata and post operative histopathology data to evaluate conformity relationship between TIRADS and post operativehistopathological result of thyroid nodule.There is comparable result (p=0.065) between TIRADS result and post operativehistopathological result of thyroidnodule. TIRADS resulted in 96.4% sensitivity; 83.0% specificity; 85.7% positive predictive value; dan 95.7% negativepredictive value.Conclusion: TIRADS can be implemented in evaluation, and reporting of thyroid ultrasonography result with gooddiagnostic value.